Analysis and Optimization of the Resistance of FF Transmission System - Mo Yimin; Xiang Kepeng; Yao Liang; Chen Longlong; Gao Yong (Jixie chuandong)
The performance of vehicle transmission system has great influence on fuel consumption of the vehicle. In order to reduce the resistance of transmission system and the fuel consumption,a research experimental about resistance for front engine front drive（ FF） transmission system is carried out on the four-drive and five-motor bench. The experimental results show,the resistance of the vehicle is positive correlated with gear level and engine speed. And the largest resistant part of vehicle transmission system is the gearbox. Then,the efficiency experiment is carried out on the lubricating oil that has influence on transmission system efficiency,and the gearbox efficiency under the condition of four different kinds of lubricating oil is compared,it is found that the optimized lubricating oil is 2#. Through the experiment,it is concluded that the comprehensive efficiency of this oil is increased by 0. 43% comparing to original oil.